“Tranq-dope” overdose and mortality: lethality induced by fentanyl and xylazine - Smith, Mark A.; Biancorosso, Samantha L.; Camp, Jacob D.; Hailu, Salome H.; Johansen, Alexandra N.; Morris, Mackenzie H.; Carlson, Hannah N. (Frontiers in Pharmacology, 2023)
Introduction: The recreational use of fentanyl in combination with xylazine (i.e., “tranq-dope”) represents a rapidly emerging public health threat characterized by significant toxicity and mortality. This study quantified the interactions between these drugs on lethality and examined the effectiveness of potential rescue medications to prevent a lethal overdose. Methods: Male and female mice were administered acute doses of fentanyl, xylazine, or their combination via intraperitoneal injection, and lethality was determined 0.5, 1.0, 1.5, 2.0, and 24 h after administration. Both fentanyl and xylazine produced dose-dependent increases in lethality when administered alone. Results: A nonlethal dose of fentanyl (56 mg/kg) produced an approximately 5-fold decrease in the estimated LD50 for xylazine (i.e., the dose estimated to produce lethality in 50% of the population). Notably, a nonlethal dose of xylazine (100 mg/kg) produced an approximately 100-fold decrease in the estimated LD50 for fentanyl. Both drug combinations produced a synergistic interaction as determined via isobolographic analysis. The opioid receptor antagonist, naloxone (3 mg/kg), but not the alpha-2 adrenergic receptor antagonist, yohimbine (3 mg/kg), significantly decreased the lethality of a fentanyl-xylazine combination. Lethality was rapid, with death occurring within 10 min after a high dose combination and generally within 30 min at lower dose combinations. Males were more sensitive to the lethal effects of fentanyl-xylazine combinations under some conditions suggesting biologically relevant sex differences in sensitivity to fentanyl-xylazine lethality. Discussion: These data provide the first quantification of the lethal effects of “tranq-dope” and suggest that rapid administration of naloxone may be effective at preventing death following overdose.